Potential role of N-benzylcinnamide in inducing neuronal differentiation from human amniotic fluid mesenchymal stem cells. (1st January 2016) - Thangnipon, Wipawan; Puangmalai, Nicha; Suwanna, Nirut; Soi-ampornkul, Rungtip; Phonchai, Ruchee; Kotchabhakdi, Naiphinich; Mukda, Sujira; Phermthai, Tatsanee; Julavijitphong, Suphakde; Tuchinda, Patoomratana; Nobsathian, Saksit
Highlights: PT-3 in combination with BMP-9 elevated βIII-tubulin and ChAT expression in the differentiation process. PT-3 in combination with BMP-9 increased p 53, but decreased Notch1 and SIRT1 levels. The effects of PT-3 in combination with BMP-9 may involve activation of ERK1/2 and PI3K/Akt. PT-3 may provide a useful adjuvant in BMP-9-induced transdifferentiation of AF-MSCs into ultimately cholinergic neurons. Abstract: Neurodegenerative disorders are characterized by chronic and progressive loss of neurons in structure and function related to aging, such as Alzheimer's disease, the latter characterized by the degeneration of cholinergic neurons in basal forebrain connected to the cerebral cortex and hippocampus. Amniotic fluid mesenchymal stem cells (AF-MSCs) have been proposed as one of the candidates for stem cell therapy of nervous system disorders. This study demonstrates that incubation of AF-MSCs, obtained from 16 to 20 week pregnant women, with 10 ng/ml bone morphogenetic protein (BMP)-9 for 48 h in conditioned medium resulted in transdifferentiation to cholinergic neuronal-like cells. This phenomenon could also be obtained with N -benzylcinnamide (PT-3). Pre-treatment for 1 h with 10 nM PT-3 augmented BMP-9 transdifferentiation effect, elevated βIII-tubulin cell numbers and fluorescence intensity of immunoreactive ChAT, ameliorated BMP-9-related production of reactive oxygen species and enhanced anti-apoptosis status of the neuronal-like cells. The transdiffirentiation process was accompanied by increased p53 but decreased Notch1 and SIRT1 ( p 53 deacetylase) levels, and activation of p 38, ERK1/2 MAPK, and PI3K/Akt pathways, in concert with inactivation of JNK, all of which were accentuated by PT-3 pre-treatment. These findings suggest that N -benzylcinnamide may provide a useful adjuvant in BMP-9-induced transdifferentiation of AFMSCs into ultimately cholinergic neurons.